Forage yield of three genotypes of Lotus corniculatus L., according to age at cut - Hernández-Guzmán, Filogonio Jesús; Alvarez- Vázquez, Perpetuo; Flores-Naveda, Antonio; Camposeco-Montejo, Neymar; Wilson-García, Claudia Yanet; Martínez-Martínez, Ricardo (Ecosistemas y Recursos Agropecuarios, 2021)
The objective was to determine the effect of the cutting moment on the productive response of three genotypes of L. corniculatus. The design was completely randomized, with three replications. The highest and lowest yields were presented at 35 and 7 DDR with 5.48 and 0.72 g DM plant-1. The blade was the one that contributed the most to the performance. The highest and lowest leaf:stem ratio  was recorded at 7 (5.71) and 42 RDD (2.39),  with the 255301 genotype being superior to the rest p > 0.05). The height and weight of the stem increased from 7 and 49 RDD. In conclusion, the  harvest age affected the L. corniculatus genotypes,  with 255301 being greater than the rest of the  genotypes in height, leaf: stem ratio, and weight per  individual stem, not in forage yield and botanical and morphological composition.